Studies on Homalomeneae (Araceae) of Borneo XXIX — Homalomena latisinus, a new species for the Borneensis Complex from Brunei - Wong, Sin Yeng; Peter C., Boyce (Firenze University Press, 2023)
The Homalomena Borneensis Complex of the Homalomena Cyrtocladon Clade (Ng et al. 2011: 26; Wong et al. 2013a; Wong et al. 2013b: 10) currently comprises five described species, all restricted to Borneo: Homalomena borneensis Ridl. (Ridley 1905: 173), H. clandestina P.C.Boyce, S.Y.Wong & Fasih. (Boyce et al. 2010: 277), H. ibanorum S.Y.Wong & P.C.Boyce (Wong et al. 2013: 18), H. ovata Engl. (Engler 1879: 296), and H. tirtae Asih, Kurniawan & P.C.Boyce, (Asih et al. 2012: 241). Here we describe a sixth species from damp kerangas in Brunei which is highly distinctive in the complex by the glossy deep green leaf blades with well-developed posterior lobes separated by a wide parabolic sinus. Hitherto only H. ibanorum has glossy leaf blades, but differs from the species described here by, among other characteristic, a weakly cordate to almost truncate base to the leaf blades. Geology in this paper is specified based on Hutchinson (1989, 2005) and Tate (2001).